Intelligent solutions for sustainable power grids - Kumar, L. Ashok 1976-; Angalaeswari, S. 1981-; Sundaram, K. Mohana; Bansal, Ramesh C.; Patil, Arunkumar 1985- (Advances in computer and electrical engineering (ACEE) book series, 2024)
Intelligent solutions for sustainable power grids focuses on emerging research areas, this book addresses the uncertainty of renewable energy sources, employs state-of-the-art forecasting techniques, and explores the application of AI techniques for enhanced power system operations. From economic aspects to the digitalization of power systems, the book provides a holistic approach. Tailored for undergraduate and postgraduate students as well as seasoned researchers, it offers a roadmap to navigate the intricate landscape of modern power systems. Dive into a wealth of knowledge encompassing smart energy systems, renewable energy integration, stability analysis of microgrids, power quality enhancement, and much more. This book is not just a guide; it is the solution to the pressing challenges in the dynamic field of energy systems.